PERANCANGAN BUKU POP-UP ALAT TRANSPORTASI TRADISIONAL PALEMBANG - Fatimatuzzahrah Fatimatuzzahrah; Mukhsin Patriansyah; Aryanto Aryanto (Besaung : Jurnal Seni Desain dan Budaya, 2016)
Traditional transportation of Palembang is now being replaced by modern transportation so the traditional transportation of Palembang has been forgotten by people. As the successor generation, we have to keep the traditions and the local cultures by still using traditional transportation which is currently still to be found. But in fact, some people have started to forget the traditional transportation, and haven’t introduced the traditional transportation to their children. Therefore, it was designed an appropriate educational media for early childhood, that is a pop-up book that can stimulate the curiosity of the children and also train the child's imagination. Pop-up book themed traditional transportation of Palembang is as an educational media for the children by introducing traditional transportation of Palembang and is as one of the effort to preserve the tradition of using traditional transportation of Palembang.